Tunable thermal conductivity of ternary alloy semiconductors from first-principles. (4th June 2021) - De Santiago, Francisco; Raya-Moreno, Martí; Miranda, Álvaro; Cruz-Irisson, Miguel; Cartoixà, Xavier; Rurali, Riccardo
Abstract: We compute the thermal conductivity, κ, of five representative III–V ternary alloys—namely In x Ga1 − x As, GaAs1 − x P x, InAs1 − x Sb x, GaAs1 − x N x, and GaP1 − x N x —in the whole range of compositions, and in zincblende and wurtzite crystal phases, using a first-principles approach and solving the phonon Boltzmann transport equation beyond the relaxation time approximation. We discuss the tunability of the thermal conductivity with the composition of the alloy, reporting a steep decrease in the thermal conductivity, followed by a wide plateau and a steep increase common in systems with lattice disorder. We also test the approximation consisting in considering impurities at small values of x as bare mass defects, neglecting their chemical identity, and discuss its validity.